การศึกษาสภาพและพฤติกรรมการใช้เทคโนโลยีสารสนเทศของนักเรียนมัธยมศึกษา ที่มีความบกพร่องทางสายตาในโรงเรียนสอนคนตาบอดกรุงเทพ - ณัฐบวร สืบเนตร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To study (1) the use of information technology at Bangkok School for the Blind (2) relationships between a physical environment and a learning environment toward grade point average (GPA) of eye disable secondary school students (3) relationships between behaviors of using information technology and instructional media toward grade point average (GPA) of eye disable secondary school students. The samples of this research were 68 eye disable secondary school students at Bangkok School for the Blind. There were two research instruments including the questionnaire and the interview. The questionnaire had questions focusing on the topics about the physical environment, the learning environment, and behaviors of using information technology. The interview had questions asking for fact, opinion, and suggestion about the state and behaviors in using information technology of eye disable secondary school students at Bangkok School for the Blind. The research analysis reported frequency, percentage and pearson product moment correlation coefficient. The research findings were summarized as follows: 1. The state of learning environment affects to grade point average (GPA) of eye disable secondary school students at 0.05 level of significance. 2. The behaviors of using instructional media affects to grade point average (GPA) of eye disable secondary school students at 0.05 level of significance. 3. The behaviors of using information technology affects to grade point average (GPA) of eye disable secondary school students at 0.05 level of significance. However, The state of physical environment did not affect to grade point average (GPA) of eye disable secondary school students at level of significance. In the interview, students reported that there was a limitation in the numbers of computers. Also, students were interested in new technologies, but they faced the problem that they did not know how to operate them. The suggestion was made that the training is needed.